A descriptive study on oral hygiene practice and caries increment in children with growth stunting - Putri, Tri Nugrahaeni; Indriyanti, Ratna; Setiawan, Arlette Suzy (Frontiers in Oral Health, 2023)
Introduction Stunting is a condition of malnutrition in children from the womb to the early life stage that causes growth failure in the body and brain. Stunting influences the development and integrity of the oral cavity and increases the risk of developing diseases in the oral cavity, such as dental caries. The growth barriers in stunting children and parental knowledge can affect maintaining oral hygiene. This study aims to determine the description of oral hygiene practice and caries increment in children with growth stunting. Methods This type of research is a quantitative descriptive with a Secondary Data Analysis approach in the form of examination results for the presence or absence of caries through the ICDAS index and the results of the oral hygiene practice questionnaire on 113 children with growth stunting in Sukajadi district, Bandung. Results Most stunting children (60.2%) experienced increased caries rates classified as low, and 70.8% had poor oral hygiene practices. There were 50 children (44.3%) with poor oral hygiene practice with low caries increment, while 18 children (15.9%) had good oral hygiene practice with low caries increment. Conclusion Oral hygiene practice is classified as poor, but caries increment is still relatively low in most stunting children in Sukajadi district, Bandung.